Inequities in birth registration, violent discipline, and child labour by disability status and sex: Evidence from the Multiple Indicator Cluster Surveys in 24 countries. - Amiya Bhatia; Calum Davey; Tess Bright; Sara Rotenberg; Emily Eldred; Claudia Cappa; Hannah Kuper; Karen Devries (Public Library of Science (PLoS), 2023)
Nearly 240 million children are estimated to have a disability globally. We describe inequities by disability status and sex in birth registration, child labour, and violent discipline outcomes. Data come from Round 6 of the Multiple Indicator Cluster Survey programme and includes 323,436 children, aged 2-17 years in 24 countries. We estimated non-registration of birth, child labour, and violent discipline, stratified by sex and disability in each country. We estimated age-adjusted prevalence ratios and prevalence differences, accounting for survey design, to calculate inequities by disability. There was large variation across countries in the percentage of children with disabilities (range: 4% to 28%), in non-registration (range: 0% to73%), child labour (range: 2% to 40%), and violent discipline (range: 48% to 95%). We found relative inequities by disability in birth registration in two countries among girls and one country among boys, and in birth certification in two countries among girls and among boys. Child labour was higher among girls with disabilities in two countries and among boys in three countries. We found larger and more prevalent inequities by disability in hazardous labour in six countries among girls (aPR range: 1.23 to 1.95) and in seven countries among boys (aPR range: 1.24 to 1.80). Inequities in the prevalence of violent discipline by disability were significant in four countries among girls (aPR range: 1.02 to 1.18) and among boys (aPRs: 1.02 to 1.15) and we found inequities in severe punishment nine countries among girls (aPR range: 1.12 to 2.27) and in 13 countries among boys (aPRs: 1.13 to 1.95). Context specific research is needed to understand the large variations in inequities by disability status and sex within and across countries. Monitoring inequities in child rights by disability status and sex is important to achieve the SDGs and ensure child protection programs reduce inequities.